Academic Failure and Child-to-Parent Violence: Family Protective Factors - Ibabe, Izaskun (Frontiers in Psychology, 2016)
A reduction in academic achievement over the course of adolescence has been observed. School failure is characterized by difficulties to teaching school goals. A variety of other behavioural problems are often associated with school failure. Child-to-parent violence has been associated with different school problems. The main objective of current study was to examine the contribution of family variables (parental education level, family cohesion, and positive family discipline) on academic failure and child-to-parent violence of adolescents from a community sample. Moreover, a goal was to explore if academic failure was a valid predictor of child-to-parent violence. To this end, it has been developed a comprehensive statistical model through Structural Equation Modeling (SEM). Participants were 584 children from eight secondary schools in the Basque Country (Spain) and aged between 12 and 18. Among other scales Conflict Tactics Scale and Family Environment Scale were administrated for measuring child-to-parent violence and family cohesion environment, respectively. The structural model revealed that parental education level is a relevant protective factor against academic failure. Positive family discipline (inductive discipline, supervision and penalty) show a significant association with child-to-parent violence and academic failure. Disciplinary practices could be more efficient to prevent child-to-parent violence or school failure if children perceive a positive environment in their home. However, these findings could be explained by inverse causality, because some parents respond to child-to-parent violence or academic failure with disciplinary strategies. School failure had indirect effects on child-to-parent violence through family cohesion. For all that, education policies should focus on parental education courses for disadvantaged families in order to generate appropriate learning environments at home and to foster improvement of parent-child relationships.